Power games political blogging in Malaysian national elections - Hah, Foong Lian (ISEAS Yusof Ishak Institute, 2016)
In order to obtain a better understanding of the much-touted democratizing effects of online media, this book employs an alternative lens to examine the use of new media at the intersection of social and political realities. It explores the ways individual political bloggers, Facebookers and Twitterers used cyberspace to battle for voter support in the 2008 and 2013 Malaysian national elections.